Catalog of the Neuropterida of India (Insecta: Neuroptera, Megaloptera, Raphidioptera) - Wachkoo, Aijaz Ahmad; Kaur, Simarjit; Akbar, Shahid Ali; Hassan, Muhammad Asghar; Pandher, Manpreet Singh; Oswald, John D. (Zootaxa, 2024)
A catalog of the species and subspecies of Neuropterida (Insecta: Neuroptera, Megaloptera, and Raphidioptera) occurring in modern India is presented, based primarily on an extensive review of relevant literature published through mid 2024. The currently known extant fauna comprises 3 orders, 15 families, 129 genera, 368 species, and 6 subspecies (Neuroptera: 11 families, 119 genera, 332 species; Megaloptera: 2 families, 8 genera, 31 species; Raphidioptera: 2 families, 2 genera, 5 species). In addition, one extinct species is known, †Spiloconis eominuta (Neuroptera: Coniopterygidae). Catalog entries contain taxonomic, synonymical, and nomenclatural data for all nominal taxa, and geographical occurrence data are provided for all valid species and subspecies. There are 171 species (46% of the fauna) presently known only from India that are possibly endemic, and 25 species previously reported from the country are excluded from the fauna.